The Abjected Feminine as a Threat to God in César Dávila Andrade’s “La mirada de Dios” - Vela, Alejandra (2020)
In this work, the author analyses the short story La mirada de Dios (1949) by Ecuadorian writer César Dávila Andrade, known as the Fakir. It suggests the coexistence of two forces in dispute: a feminine force represented by spaces which act as metaphors of Doña Emperatriz’ body; the other is a patriarchal force embodied by God’s gaze. The sexual relationship between the characters, Doña Emperatriz and the priest, challenges social positions, allowing them to enter into an abject feminine space where the limits imposed by power lose their strength. It uses Mary Douglas’ notions of “purity” and “impurity” extended upon by Julia Kristeva, to understand how the femenine realm is constituted in the impure and, is therefore a threat to the hegemonic system.